The Titanic : an interactive history adventure - Temple, Bob (You choose books., 2008)
Describes the events surrounding the sinking of the ship Titanic in 1912. The reader's choices reveal the historical details from the perspective of a first-class passenger, a third-class passenger, and a crewmember.